What Affects People's Willingness to Participate in Qualitative Research? An Experimental Comparison of Five Incentives. Issue 4 (November 2017) - Kelly, Bridget; Margolis, Marjorie; McCormack, Lauren; LeBaron, Patricia A.; Chowdhury, Dhuly
The literature on factors that influence participation in qualitative research is lacking. We conducted an experiment with a nationally representative sample to test the impact of different incentive types and amounts on willingness to participate in a hypothetical qualitative interview. We randomized participants from an online panel to one of the five versions of a recruitment ad: no incentive, a nonmonetary incentive, US$25, US$50, or US$75 ( N = 4, 136). All three monetary incentives resulted in greater willingness to participate than no incentive or a nonmonetary incentive. No differences emerged between no incentive and a nonmonetary incentive (drawing for noncash prize). Among those who had at least some willingness, US$75 produced more willingness than US$25. The US$50 and US$75 amounts did not differ. Results suggest incentives matter in achieving participation in qualitative research, but there may be diminishing returns. Nonmonetary incentives may not result in higher participation than no incentive at all.